Orbital Phase Shifts of Type-I Outbursts in EXO 2030+375 - Run-Ting Huang; Long Ji; Jing-Zhi Yan (The Astrophysical Journal)
EXO 2030+375 is a peculiar high-mass X-ray binary that has been exhibiting Type-I outburst activities consistently over the past decades. The phases of outburst peaks are generally stable and occur near the orbital periastron. However, significant orbital phase shifts have occasionally been observed in 1995, 2006, and 2016. In this paper, we report another orbital phase shift triggered by a giant outburst in 2021. During this event, the orbital phase of Type-I outburst peaks changed dramatically, moving from near periastron to 20 days after periastron, followed by a gradual recovery. Additionally, for several cycles after the 2021 giant outburst, some Type-I outbursts were missing, with subsequent outbursts occurring every two orbits. We discuss our observations in the frame of the precession of an eccentric Be disk.